Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J (Entomologia Experimentalis et Applicata, 2013)
The longhorn beetle, Cerambyx welensii Küster (Coleoptera: Cerambycidae), is an emerging pest involved in oak decline episodes in dehesa open woodlands. Larvae are xylophagous and cause considerable physiological, mechanical, and structural damages to trees. Chemical and biological control are currently unsatisfactory. Recent research has shown that mass trapping with a high density of baited traps (40 traps ha−1) could be useful to manage C. welensii populations, although such a trap density was too high to be cost-effective. In this 2-year study (2010–2011) we investigated with mark–recapture methods in a large plot (1) the flight dispersal behaviour, (2) the adult population density, and (3) the efficiency of mass trapping at two low trap densities (one or four traps ha−1). Results indicated that many adults were sedentary (60%) but flying adults displayed a strong propensity to move, both sexes dispersing on average more than 200 m and one male and one female flying at least 540 and 349 m, respectively. Recapture rates were high (0.26–0.35) and population density was estimated to be 6–22 adults ha−1 with maximum likelihood models. Trapping efficiency ranged 48–61% with no significant effect of trap density or year. We conclude that results were not satisfactory enough to recommend mass trapping with low trap densities as control method for C. welensii and that more research is still required on the technical, ecological, and behavioural factors affecting control efficiency.
From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )
Keywords: cerambycidae; Coleoptera; Fagaceae; Holm oak; longhorn beetle; ml secr models; Oak decline; open woodland; pest control

Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. (Entomologia Experimentalis et Applicata, 2013)
The longhorn beetle, Cerambyx welensii Küster (Coleoptera: Cerambycidae), is an emerging pest involved in oak decline episodes in dehesa open woodlands. Larvae are xylophagous and cause considerable physiological, mechanical, and structural damages to trees. Chemical and biological control are currently unsatisfactory. Recent research has shown that mass trapping with a high density of baited traps (40 traps ha−1) could be useful to manage C. welensii populations, although such a trap density was too high to be cost-effective. In this 2-year study (2010–2011) we investigated with mark–recapture methods in a large plot (1) the flight dispersal behaviour, (2) the adult population density, and (3) the efficiency of mass trapping at two low trap densities (one or four traps ha−1). Results indicated that many adults were sedentary (60%) but flying adults displayed a strong propensity to move, both sexes dispersing on average more than 200 m and one male and one female flying at least 540 and 349 m, respectively. Recapture rates were high (0.26–0.35) and population density was estimated to be 6–22 adults ha−1 with maximum likelihood models. Trapping efficiency ranged 48–61% with no significant effect of trap density or year. We conclude that results were not satisfactory enough to recommend mass trapping with low trap densities as control method for C. welensii and that more research is still required on the technical, ecological, and behavioural factors affecting control efficiency.
From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )
Keywords: cerambycidae; Coleoptera; Fagaceae; Holm oak; longhorn beetle; ml secr models; Oak decline; open woodland; pest control

Impact of stand density on water status and leaf gas exchange in Quercus ilex - Moreno, Gerardo; Cubera, Elena (Forest Ecology and Management, 2008)
Tree thinning reduces tree-to-tree competition and likely contributes to the improvement of tree water status and productivity in water-limited systems. In this study, we examined the importance of competition for water among Quercus ilex trees in open woodlands by comparing the water consumption and physiological status of trees located along stand density gradients which ranged from 10% (low density; LD) to 100% (high density; HD) of canopy cover. The study was carried out at two sites which differed in mean annual rainfall (506 and 816 L m 2 ; Dsite and Wsite , respectively). Predawn and midday leaf water potential (cd and cm, respectively) and CO2 assimilation rate (A) were measured every two weeks from mid May to mid September, in eight trees located along a stand density gradient at each site. Sap ﬂow and soil moisture were measured only at Dsite . Sap ﬂow was continuously recorded by sap ﬂowmeters (constant heating method) installed in 12 trees along two stand density gradients. Soil moisture (U) was measured every 20 cm for the ﬁrst meter and then every 50 cm up to 250 cm. Measurements were conducted in 18 soil proﬁles, 6 located in HD and 12 in LD (six beneath and six out the canopy). At Wsite , differences among stand densities for c and A were very small and emerged only at the end of the dry season. At Dsite , c (both predawn and midday), A, U, and sap ﬂow density were signiﬁcantly higher in LD trees than in HD ones. At Dsite , some water remained unused in the soil at the end of the dry season beyond the canopy in the LD areas, and trees did not experienced such an acute water deﬁcit (cd > 1 MPa) as the HD trees did (cd < 3 MPa). Summer tree transpiration at the stand level (Estand) tended to saturate with the increase of canopy cover. Estand increases by 32% when canopy cover goes from 50% to 100%. Results conﬁrmed that the increase of tree-to-tree competition with stand density was much more signiﬁcant at dry sites. In these sites, tree thinning is recommended as a way to maintain tree functioning
Keywords: leaf water potential; open woodland; photosynthesis; sap flow; Soil moisture

Impact of stand density on water status and leaf gas exchange in Quercus ilex - Moreno, Gerardo; Cubera, Elena (Forest Ecology and Management, 2008)
Tree thinning reduces tree-to-tree competition and likely contributes to the improvement of tree water status and productivity in water-limited systems. In this study, we examined the importance of competition for water among Quercus ilex trees in open woodlands by comparing the water consumption and physiological status of trees located along stand density gradients which ranged from 10% (low density; LD) to 100% (high density; HD) of canopy cover. The study was carried out at two sites which differed in mean annual rainfall (506 and 816 L m 2 ; Dsite and Wsite , respectively). Predawn and midday leaf water potential (cd and cm, respectively) and CO2 assimilation rate (A) were measured every two weeks from mid May to mid September, in eight trees located along a stand density gradient at each site. Sap ﬂow and soil moisture were measured only at Dsite . Sap ﬂow was continuously recorded by sap ﬂowmeters (constant heating method) installed in 12 trees along two stand density gradients. Soil moisture (U) was measured every 20 cm for the ﬁrst meter and then every 50 cm up to 250 cm. Measurements were conducted in 18 soil proﬁles, 6 located in HD and 12 in LD (six beneath and six out the canopy). At Wsite , differences among stand densities for c and A were very small and emerged only at the end of the dry season. At Dsite , c (both predawn and midday), A, U, and sap ﬂow density were signiﬁcantly higher in LD trees than in HD ones. At Dsite , some water remained unused in the soil at the end of the dry season beyond the canopy in the LD areas, and trees did not experienced such an acute water deﬁcit (cd > 1 MPa) as the HD trees did (cd < 3 MPa). Summer tree transpiration at the stand level (Estand) tended to saturate with the increase of canopy cover. Estand increases by 32% when canopy cover goes from 50% to 100%. Results conﬁrmed that the increase of tree-to-tree competition with stand density was much more signiﬁcant at dry sites. In these sites, tree thinning is recommended as a way to maintain tree functioning
Keywords: leaf water potential; open woodland; photosynthesis; sap flow; Soil moisture

Effects of trees and understorey management on soil fertility and nutritional status of holm oaks in Spanish dehesas - Moreno, Gerardo; Obrador, José Jesús (Nutrient Cycling in Agroecosystems, 2007)
A dehesa is a multipurpose agroforestry system with scattered oaks. This study focuses on the inﬂuence of trees on soil chemical fertility and on the consequences of dehesa land use for soil fertility and nutritional status of trees. To achieve that we have studied the content of several nutrients in soils and tree leaves in four Spanish dehesas, considering three types of land use: scattered holm oak with an understorey of either native grasses (G), shrubs (E) or crop (C: either fertilized or unfertilized). We randomly selected six oaks per farm and land use for soil and tree leaf sampling. Soil samples were taken at ﬁve distances from each tree trunk (2, 5, 10, 15, and 20 m) at a depth of 0–30 cm. SOM, CEC, total and mineral-N, available-P, and exchangeable Ca, Mg and K were analysed. Foliar samples were collected from every tree in two consecutive years (2002 and 2003) at leaf maturity. The total content of N, P, K, Ca, and Mg was determined. Soils of C plots showed signiﬁcantly higher contents for most of the nutrients studied than G ones. Cropping also affected trees positively, with higher foliar contents of N and K in C plots than in G ones. Foliar content did not decrease for any nutrient, and tree-crop interaction is interpreted as a mechanism of complementarity in terms of nutrient use. Shrub encroachment led to a higher content of organic-N and exchangeable cations in soils, but to a decrease in mineral N and available-P. The tree foliar contents of N, Mg, and Ca were lower in E plots than in G plots, probably as a consequence of the tree-shrub competition for those nutrients. By contrast, P content of tree leaves increased signiﬁcantly in E plots compared to G plots.
Keywords: Encroachment; Intercrop; Nutrient pump; open woodland; Tree-understorey interaction